The dynamics of small bodies in the solar system : a major key to solar system studies - Steves, Bonnie A.; Roy, A. E. (Archie E.), 1924-2012 (NATO ASI series. Mathematical and physical sciences, 1999)
The study of the nature and dynamics of asteroids, comets, meteor streams, natural satellites and ring systems currently provides a wealth of information on the history and dynamical evolution of the solar system as a whole. This state of the art textbook, based on the recent NATO ASI The Dynamics of Small Bodies in the Solar System and written by the invited lecturers and other participants, provides an invaluable reference volume for all students and researchers in these subjects. The contributions are introduced by specially written reviews from renowned experts in their fields. It is evident that the majority of dynamical astronomers and space researchers interested in solar system studies are currently involved with the study of small natural and artificial bodies in the solar system, and this volume presents them with an up-to-date, synoptic view of these subjects.